Kontribusi Daya Ledak Otot Lengan dan Koordinasi Mata-Tangan terhadap Ketepatan Smash Atlet Bulutangkis Junior PB. Wahyudan Kabupaten Solok Selatan - Redi, Aidil Ariesto; Maidarman, M; Masrun, M; Edmizal, Eval (Universitas Negeri Padang, 2024)
This study aims to determine the contribution of arm muscle explosiveness and hand eye coordination to the Accuracy of Smash Junior Badminton Athletes PB. Wahyudan South Solok Regency which amounted to 16 people. The instruments in this study used the Overhead Medicine Ball Throw test, tennis ball throwing catch, and badminton smash accuracy. The results of the calculations obtained by the correlation index with the results of X1 data on Y amounted to = 0.670 with the calculation of rcount = 0.670> rtable = 0.425 thus the results obtained were significant which had a contribution of 45%. For X2 on Y of 0.600, the calculation of rcount = 0.600> 0.425 thus the results obtained are significant with a contribution of 36%. While the results of the calculation of X1 and X2 on Y rcount of 0.741> rtable 0.425. So the contribution of arm muscle explosiveness and hand eye coordination to the accuracy of smash of Badminton Athletes PB Wahyudan South Solok Regency is 57%, thus the results obtained are significant. Keywords: Arm Muscle Explosiveness, Hand Eye Coordination, Smash Accuracy